2020
DOI: 10.1002/pbc.28251
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of step‐down to oral outpatient treatment versus inpatient antimicrobial treatment in pediatric cancer patients with febrile neutropenia: A noninferiority multicenter randomized clinical trial

Abstract: Background It has been suggested that low‐risk febrile neutropenia (FN) episodes can be treated in a step‐down manner in the outpatient setting. This recommendation has been limited to implementation in middle‐income countries due to concerns about infrastructure and lack of trained personnel. We aimed to determine whether early step‐down to oral antimicrobial outpatient treatment is not inferior in safety and efficacy to inpatient intravenous treatment in children with low‐risk FN. Procedure A noninferiority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…When each study was analyzed individually, however, only two of them [ 12 , 24 ] listed Gram-positive bacteria as being the primary pathogen of their MDI, while all the rest described Gram-negative bacteria to be the leading cause of the infections, with Gram-positive pathogens taking up the second place. The third place was occupied by fungi in all but one study [ 14 ], where there were more fungi identified as Gram-positive bacteria. This can be seen in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When each study was analyzed individually, however, only two of them [ 12 , 24 ] listed Gram-positive bacteria as being the primary pathogen of their MDI, while all the rest described Gram-negative bacteria to be the leading cause of the infections, with Gram-positive pathogens taking up the second place. The third place was occupied by fungi in all but one study [ 14 ], where there were more fungi identified as Gram-positive bacteria. This can be seen in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Either way, prompt empiric broad-spectrum antibiotic administration is collectively recommended by the FN guidelines and professional medical societies [ 11 , 12 , 13 ]. The increased duration until antibiotic administration is initiated has been associated, in the pediatric setting, with higher rates of sepsis and higher rates of intensive care admission and death, thus prompting the term “golden hour” as the recommended timeframe between FN patient presentation to the start of the antibiotic administration [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Thus, not erring on the side of safety (including local peculiarities, such as distance from home to the next point of care) leaves only 10-20% of all patients eligible. 1,8 How to move forward? The local standards for blood culture diagnostic should be updated and optimized.…”
mentioning
confidence: 99%
“…To the Editor: We thank Avilés‐Robles et al 1 for their interesting study, addressing the safety and efficacy of step‐down to oral outpatient treatment versus inpatient antimicrobial treatment in pediatric cancer patients (pCP) with febrile neutropenia (FN). This study from Mexico City adds very important data to carefully adjust the current standard of clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation